1997
DOI: 10.1590/s1413-77391997000100004
|View full text |Cite
|
Sign up to set email alerts
|

Benthic communities of shallow-water reefs of Abrolhos, Brazil

Abstract: The benthic communities of fringing and mushroom-shaped shallow-water reefs of the Abrolhos region (southern coast of Bahia) were surveyed. Line transects were used to estimate coral and algal percentage cover. Mussismilia braziliensis is the most conspicuous coral species in the majority of the communities surveyed, but turf algal make up the dominant cover in all but one studied reef. In general, communities on mushroom-shaped reefs have higher diversity and higher coral cover than on fringing reefs. For bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 8 publications
6
45
0
7
Order By: Relevance
“…Similarly to what was found in previous studies in the northeastern Brazilian coast, Ochrophyta were the most abundant macroalgae in the TSB (Coutinho et al 1993, Amado Filho et al 1997a, Villaça & Pitombo 1997, Muñoz & Pereira 1998, Figueiredo 2000, Costa Jr. et al 2002, Villaça 2002, Paula et al, 2003.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly to what was found in previous studies in the northeastern Brazilian coast, Ochrophyta were the most abundant macroalgae in the TSB (Coutinho et al 1993, Amado Filho et al 1997a, Villaça & Pitombo 1997, Muñoz & Pereira 1998, Figueiredo 2000, Costa Jr. et al 2002, Villaça 2002, Paula et al, 2003.…”
Section: Discussionsupporting
confidence: 84%
“…This is one of the most commonly found calcified algae found in coral reefs of the Brazilian northeastern coast (Leão 1982, Carvalho 1983, Martins et al 1991, Coutinho et al 1993, Villaça & Pitombo 1997, Costa Jr. et al 2002, besides being one of the most common taxa found in coral reefs (Lirman 2001) and one of the most important sources of carbonates to the reef systems (Adey 1998, Villaça 2002.…”
Section: Discussionmentioning
confidence: 99%
“…At approximately 17ºS, the continental shelf widens to form the Abrolhos Bank on which the richest and best known coral reefs of the eastern Brazilian region are located (HARTT, 1870;LABOREL, 1970, LEÃO, 1983LEÃO et al 1988, LEÃO et al, 1996, 1999GINSBURG, 1997;PITOMBO, 1997;PITOMBO et al, 1988;KIKUCHI, 2001;LEÃO et al, 2003LEÃO et al, , 2006FOURNIER, 2007;LEÃO et al, 2008;FRANCINI-FILHO et al, 2008among others). These reefs form the following two arcs: the coastal arc composed of bank reefs of various shapes and dimensions and the outer arc eastward of the islands of the Abrolhos Archipelago, which is formed by isolated "chapeirões" in water deeper than 20 m. Incipient fringing reefs border the shores of the five islands that compound the archipelago (Figures 9 and 10).…”
Section: Major Coral Reef Types and Their Distributionmentioning
confidence: 99%
“…Due to its high abundance, colour pattern and large size, it is one of the most conspicuous and recognizable species of the family Pomacanthidae in the Caribbean (DELOACH, 1999 (FERREIRA et al, 2004). In the South-western Atlantic, juveniles of P. paru have been reported as fish cleaners in Abrolhos, North-eastern Brazilian coast (SAZIMA et al, 1999), but a great diversity of sponges was also detected in their gut contents in Salvador, Bahia State (ANDRÉA et al, 2007) PITOMBO, 1997;MORAES et al, 2003;CREED;OLIVEIRA, 2007). Samples were collected in two large tidal pools at Atol das Rocas (Barretinha and Barreta Falsa), one fringing reef in Abrolhos (Portinho Sul), and one rocky coast on Ilha Grande (Lagoa Verde) (Fig.…”
mentioning
confidence: 99%
“…This variation appears to be related to the differences in local food availability (VERDÍN et al, 2010). In Brazil, algae are the most abundant organisms on the shallow reefs of Atol das Rocas and Abrolhos (KIKUCHI; LEÃO, 1997;MORAES et al, 2003;VILLAÇA;PITOMBO, 1997), where they are the main food of the French angelfish. The low similarity in qualitative composition of the diet between the three sites further supports the idea that diet composition is correlated to the composition of the benthic community, which varies in different localities.…”
mentioning
confidence: 99%